2020
DOI: 10.14445/22315381/cati1p214
|View full text |Cite
|
Sign up to set email alerts
|

Using Interval Manager Mobile Application in Saving Time and Cost

Abstract: The Interval Manager (INTMAN-Mobile Workforce) is a mobile-assisted Utility that replaces the traditional paper-and-pencil strategies to gather fixed c language time-sampled observational information. An initial application that compares INTMAN-Mobile Workforce with the traditional method of paper-and-pencil was presented in this article. Smart Devices were used to run INTMAN-Mobile Workforce data collection application while a Microsoft Windows run using desktop was used to analyse the data. Changed frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The current findings revealed that the respondents understood that the future stroke mobile application is a multifunctional hub that allows access to accurate and authentic sources of information, in addition to being a time-saving application. This is in line with recent research [55][56][57] that emphasized the advantages of using multipurpose mobile applications, especially in terms of time saving [58,59]. To create a paradigm shift in stroke healthcare toward achieving a proactive involvement in patient self-care practices and improving patient engagement instead of being a passive recipient of self-healthcare, the application should be able to deliver the appropriate and intelligible information according to the local environment [60,61].…”
Section: Discussionsupporting
confidence: 71%
“…The current findings revealed that the respondents understood that the future stroke mobile application is a multifunctional hub that allows access to accurate and authentic sources of information, in addition to being a time-saving application. This is in line with recent research [55][56][57] that emphasized the advantages of using multipurpose mobile applications, especially in terms of time saving [58,59]. To create a paradigm shift in stroke healthcare toward achieving a proactive involvement in patient self-care practices and improving patient engagement instead of being a passive recipient of self-healthcare, the application should be able to deliver the appropriate and intelligible information according to the local environment [60,61].…”
Section: Discussionsupporting
confidence: 71%
“…Trading involves contact between seller and buyer, supplier and customer, manufacturer and distributor, retailer and wholesaler. There are other encouraging factors that facilitate electronic trading, such as the growing use of methods of non-cash payment that do not require a physical presence, such as a credit card [10]. For even more economic globalization, multinational corporations are looking.…”
Section: Background Of Studymentioning
confidence: 99%
“…These figures indicate the volume of circulation and visits to this global platform and the continuous development, which makes it keep pace with modern technologies and dazzle its users and obtain their satisfaction. The percentages and figures also show the progress of the administrative system for this financial company to the platform while preserving the quality provided [11]. And to make it ahead of its competitors from the global platforms that provide commercial services over the Internet, eBay was created using modern and advanced distributed object technology.…”
Section: Background Studymentioning
confidence: 99%